Distal Tubulopathy. Gitelman Syndrome - Alexander A. Baranov; Leyla S. Namazova-Baranova; Tatyana V. Sergeeva; Olga V. Chumakova; Svetlana S. Paunova; Nurali Z. Zokirov; Olga V. Komarova; Tea V. Margieva; Vladimir K. Tatochenko; Maya D. Bakradze; Elena N. Tsygina; Olga I. Zrobok; et al. (Union of pediatricians of Russia, 2019)
The clinical recommendations on management of children with Gitelman syndrome developed by the experts of the Union of pediatricians of Russia are presented in this article. Gitelman syndrome is a dysfunction of distal renal tubules with further development of hypomagnesemia, hypocalciuria and secondary aldosteronism which determine hypokalemia and metabolic alkalosis. Features of epidemiology, etiology and pathogenesis, disease progression, differential diagnostics and evidence-based treatment are presented.